2023
DOI: 10.3389/fpls.2023.1070600
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary and phylogenetic analyses of 11 Cerasus species based on the complete chloroplast genome

Abstract: The subgenus Cerasus, one of the most important groups in the genus Prunus sensu lato, comprises over 100 species; however, the taxonomic classification and phylogenetic relationships of Cerasus remain controversial. Therefore, it is necessary to reconstruct the phylogenetic tree for known Cerasus species. Here, we report the chloroplast (cp) genome sequences of 11 Cerasus species to provide insight into evolution of the plastome. The cp genomes of the 11 Cerasus species (157,571–158,830 bp) displayed a typica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 64 publications
6
8
1
Order By: Relevance
“…6 ; Yang et al, 2023 ). Significant IR contractions of rps 19 and ycf 1 were observed, which were predicted as the main contributors to the overall variation observed among Myricaria chloroplast genomes, in line with reports for species in other genera, including Cerasus , Prunus and Rubus ( Yu et al, 2022 ; Wan et al, 2023 ). The comparative analysis and P i values test ( Figs.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…6 ; Yang et al, 2023 ). Significant IR contractions of rps 19 and ycf 1 were observed, which were predicted as the main contributors to the overall variation observed among Myricaria chloroplast genomes, in line with reports for species in other genera, including Cerasus , Prunus and Rubus ( Yu et al, 2022 ; Wan et al, 2023 ). The comparative analysis and P i values test ( Figs.…”
Section: Discussionsupporting
confidence: 87%
“…A total of 114–115 unique genes were annotated in this study ( Tables 1 and S1 ), including four rRNA genes, 30 tRNA genes, and 80–81 CDSs, similar to previous reports ( Liu et al, 2020b ). There were some differences in the genes annotated in this study compared to previous studies, mainly reflected in CDSs, such as ycf genes ( Wan et al, 2023 ); specifically, the ycf 15 gene was detected in 32 Myricaria samples, but absent in three individuals (codes 7301, 3010 and 2912; Table S1 ). The discrepancy in the number of PCGs in the publicly-available Myricaria plastomes may be attributed to a different annotation strategy.…”
Section: Discussioncontrasting
confidence: 61%
“…The codon usage bias of 20 amino acids among different species is similar (Fig. 2, Table S5), which is congruent with other angiosperms [67,90]. It is revealed that most protein-coding genes are generally identical, but accD, matK, ndhI, rpl22, rpl20, rpoA, rps16, rps18, ycf1 and ycf2 in J. grossa are obviously different from that in other Justicia plants in length and base variation (Table S3), suggesting J. grossa is different from other Justicia plants in plastid genes.…”
Section: Discussionsupporting
confidence: 85%
“…There were some related studies exposed ycf1 as a paramount pseudogene in plants, leading to incomplete duplication of the gene within IRs [31,36]. The ycf1 gene repeated twice in the chloroplast genome of P. Cistena, which was similar to other Prunus plants [22,37]. It has been testi ed that the introns play a signi cant role in regulating the expression of genes, which might control the gene expression level in different spatiotemporal [19,31,38].…”
Section: Discussionmentioning
confidence: 99%